(untitled) - Sanchez, Ron (Oxford, UK, 2001)
Today's management thinking is centered on two fields: knowledge management and competence-based approaches to strategic management. Drawing on research by noted scholars in the fields, this volume will provide new theoretical impetus for management researchers, while suggesting useful new methods and tools for practitioners.
Keywords: Knowledge management,Organizational learning,Organizational effectiveness